2021
DOI: 10.1038/s41598-021-82617-2
|View full text |Cite
|
Sign up to set email alerts
|

Obesity reduces the anticancer effect of AdipoRon against orthotopic pancreatic cancer in diet-induced obese mice

Abstract: The antidiabetic adiponectin receptor agonist AdipoRon has been shown to suppress the tumour growth of human pancreatic cancer cells. Because obesity and diabetes affect pancreatic cancer progression and chemoresistance, we investigated the effect of AdipoRon on orthotopic tumour growth of Panc02 pancreatic cancer cells in DIO (diet-induced obese) prediabetic mice. Administration of AdipoRon into DIO mice fed high-fat diets, in which prediabetic conditions were alleviated to some extent, did not reduce either … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(23 citation statements)
references
References 42 publications
1
22
0
Order By: Relevance
“…Conversely, deficiency or knockdown of adiponectin receptors markedly promoted PDAC xenograft growth [118,119]. Interestingly, a recent xenograft study showed that AdipoRon failed to suppress PDAC growth in mice with DIO, while it suppressed tumor growth in lean mice [120]. Taken together, a link between adiponectin and PDAC risk is not conclusively demonstrated by available epidemiologic studies.…”
Section: Adiponectinmentioning
confidence: 97%
“…Conversely, deficiency or knockdown of adiponectin receptors markedly promoted PDAC xenograft growth [118,119]. Interestingly, a recent xenograft study showed that AdipoRon failed to suppress PDAC growth in mice with DIO, while it suppressed tumor growth in lean mice [120]. Taken together, a link between adiponectin and PDAC risk is not conclusively demonstrated by available epidemiologic studies.…”
Section: Adiponectinmentioning
confidence: 97%
“…IR-A/B and IGF-1R mediate their effects through: Ras/mitogen activated protein kinase (MAPK)/extracellular signal-related kinase 1/2 (ERK-1/2) pathway; phosphoinositide 3-kinase (PI3K)/protein kinase B (Akt)/forkhead box O (FoxO) pathway; PI3K/Akt/mammalian target of rapamycin (mTOR) pathway; and PI3K/Akt-induced accumulation of the proto-oncogene β-catenin, via inactivation of its inhibitor glycogen synthase kinase 3β (GSK3β) ( 5 , 14 , 20 ) ( Figure 2 ).…”
Section: Tumor Microenvironment and Insulin-like Peptidesmentioning
confidence: 99%
“…In addition, obesity could be associated with cancer drug resistance. Obesity reduced the anti-cancer effects of the antidiabetic adiponectin receptor agonist AdipoRon in diet-induced obese mice with orthotopic pancreatic cancer through a mechanism involving IGF-1, IGF-1R, and ERK1/2 signaling ( 5 ), indicating the importance of weight loss in combating pancreatic cancer in obese patients.…”
Section: Igf-1r Signaling: a Key Link Between Metabolic Syndrome And ...mentioning
confidence: 99%
“…Standing out as the topscored in activating AMPK and bonding AdipoR1 and AdipoR2 in murine myeloblast C2C12 cells, AdipoRon is currently recognized as the first orally active adiponectin receptor agonist [67] . Independent research groups have provided convincing evidence supporting the antiproliferative role played by AdipoRon in both in vitro and in vivo PDAC models [61,[68][69][70][71] . Unsurprisingly, querying the main scientific databases for AdipoRon, PDAC represents the most mentioned among the tumor models examined thus far.…”
Section: Adiporon and Pdac: More Lights Than Shadowsmentioning
confidence: 99%